Characterization of mutations in the FOXE1 gene in a cohort of unrelated Malaysian patients with congenital hypothyroidism and thyroid dysgenesis - Kang, I.N.; Musa, M.; Harun, F.; Junit, S.M. (Kluwer (now part of Springer), 2010)
The FOXE1 gene was screened for mutations in a cohort of 34 unrelated patients with congenital hypothyroidism, 14 of whom had thyroid dysgenesis and 18 were normal (the thyroid status for 2 patients was unknown). The entire coding region of the FOXE1 gene was PCR-amplified, then analyzed using single-stranded conformational polymorphism, followed by confirmation by direct DNA sequencing. DNA sequencing analysis revealed a heterozygous A > G transition at nucleotide position 394 in one of the patients. The nucleotide transition changed asparagine to aspartate at codon 132 in the highly conserved region of the forkhead DNA binding domain of the FOXE1 gene. This mutation was not detected in a total of 104 normal healthy individuals screened. The binding ability of the mutant FOXE1 protein to the human thyroperoxidase (TPO) promoter was slightly reduced compared with the wild-type FOXE1. The mutation also caused a 5% loss of TPO transcriptional activity.